Effect of Rotation Speed Parameter on Mechanical Properties of Similar AISI 1040 Parts Joined by Friction Welding - Balalan, Z.; Ekinci, O. (Металлофизика и новейшие технологии, 2018)
Friction welding is one of the important joining methods widely used, especially for welding cylindrical parts, in many industries. In this study, friction welding of similar material steel AISI 1040 cylindrical parts having 12 mm diameter is successfully realised at different welding parameters. In order to determine mechanical properties of welds, the tensile strength and microhardness tests as well as microstructural analysis are carried out and discussed. In addition, the comparison between parts welded at different revolutions per minute (rpm) is made in terms of mechanical properties. Experimental results show that the highest tensile strength is nearly 400 MPa, which is obtained at the parts welded through 1500 rpm.